Adsorptive removal of nickel and lead ions from aqueous solutions by poly (amidoamine) (PAMAM) dendrimers (G4) - Ebrahimi, Roya; Hayati, Bagher; Shahmoradi, Behzad; Rezaee, Reza; Safari, Mahdi; Maleki, Afshin; Yetilmezsoy, Kaan (ELSEVIER, 2018)
This research is a first-time investigation into the use of poly (amidoamine) (PAMAM) dendrimers (Generation 4: G(4)) as well-designed, highly-branched macromolecules with abundant active amine groups for the adsorptive removal of nickel (Ni2+) and lead (Pb2+) from aqueous phases. The adsorption capacity and efficiency were studied under various operating conditions including a pH range of 2-7, contact time (t) of 2-12 min, initial heavy metal (Ni2+ or Pb2+) concentration (C-0) of 50-200 mg/L, and adsorbent dose (m) of 0.04-0.1 g/L were studied for the optimization and modeling of the process. The diameter, structure, and surface characteristics of PAMAM dendrimers were analyzed by Dynamic Light Scattering (DLS), Nuclear Magnetic Resonance (NMR), zeta sizer, Scanning Electron Microscope (SEM) and Fourier Transform Infrared (FTIR) spectroscopy. The adsorption mechanism and the relevant characteristic parameters were investigated by two-parameter isotherm models (Langmuir and Freundlich) and kinetic models (Lagergren's pseudo-first order and Ho and McKay's pseudo-second order). Adsorption thermodynamics of metal ions onto PAMAM dendrimers were also studied at various temperatures of 298, 308, 318, 328, and 338 K. The results showed that adsorption kinetics of Ni2+ and Pb2+ were very well described by Ho and McKay's pseudo-second order kinetic model (R-2 > 0.99). The adsorption isotherms of studied metal ions followed Freundlich model (R-2 > 0.995). According to the Langmuir model, the maximum removal capacity of PAMAM dendrimers for Ni2+ and Pb2+ ions were 1626 and 1783 mg/g, respectively. The thermodynamic evaluations demonstrated that the removal of Ni2+ and Pb2+ ions onto PAMAM dendrimers was endothermic with positive enthalpy changes of 17.048 and 16.995 kJ/mol and spontaneous with negative free energy values of -11.063 and -10.107 kJ/mol for Ni2+ and Pb2+ ions, respectively. The result indicated that PAMAM dendrimers could be applied a superior adsorbent for Ni2+ and Pb2+ removal from aqueous solutions. (C) 2018 Published by Elsevier B.
Keywords: Nickel and lead adsorption; PAMAM dendrimers; Heavy metal removal; Isotherm model; Kinetic model; WASTE-WATER; NI2+; POLYAMIDOAMINE; BIOSORPTION; CAPACITY; COPPER; ZINC; PB2+; Biotechnology & Applied Microbiology; Engineering; Environmental Sciences & Ecology